Application of Nano Fe III –Tannic Acid Complexes in Modifying Aqueous Acrylic Latex for Controlled-Release Coated Urea - Shen, Yazhen; Du, Changwen; Zhou, Jianmin; Ma, Fei (Journal of agricultural and food chemistry, 2017)
Acrylic latexes are valuable waterborne materials used in controlled-release fertilizers. Controlled-release urea coated with these latexes releases a large amount of nutrients, making it difficult to meet the requirement of plants. Herein, Fe -tannic acid (TA) complexes were blended with acrylic latex and subsequently reassembled on a surface of polyacrylate particles. These complexes remarkably retarded the release of urea (the preliminary solubility was decreased from 22.3 to 0.8%) via decreasing the coating tackiness (T was increased from 4.17 to 6.42 °C), increasing the coating strength (tensile stress was improved from 3.88 to 4.45 MPa), and promoting the formation of denser structures (surface tension was decreased from 37.37 to 35.94 mN/m). Overall, our findings showed that a simple blending of Fe -TA complexes with acrylic latex produces excellent coatings that delay the release of urea, which demonstrates great potential for use in controlled-release fertilizers coated with waterborne polymers.